Evaluasi Kebijakan Program Usaha Peningkatan Pendapatan Keluarga Akseptor (UPPKA) di Kota Gorontalo - Cha Cha Esa Agustina Wuwungan; Sri Yulianty Mozin; Yacob Noho Nani (Perspektif Administrasi Publik dan hukum, 2026)
High population growth demands sustainable family economic empowerment efforts, one of which is through the Acceptor Family Income Improvement Effort (UPPKA) Program. However, its implementation reality in Dulalowo Sub-district is characterized by the challenge of low community participation. This research aims to evaluate in-depth the extent of the program's success using the Context, Input, Process, Product (CIPP) evaluation model approach. Through the application of a descriptive qualitative method, empirical data were collected from eight informants using in-depth interviews, observation, and documentation study techniques. The research findings indicate a contradictory gap between administrative success and economic welfare stagnation in the field. Contextually, this program is highly needed by the target community, but its implementation is hindered in the input aspect due to the absence of cash operational capital support. This directly impacts a passive socialization process and triggers low citizen participation due to sociological obstacles in the form of housewives' double burden. Consequently, the program's achievement product is only limited to fulfilling the kitchen needs of a small-scale group and fails to alleviate poverty at a macro level. In conclusion, this program requires a reorientation of assistance into cash capital, accurate integration of poverty data, and strengthening of cross-sectoral collaboration.